Sexual Activity in Adolescents and Young Adults through COVID-19 Pandemic - Stavridou, Androniki (Children (Basel), 2021)
During the COVID-19 pandemic, it has been postulated that the sexual life of adolescent and young adults has been impacted in various aspects, potentially affecting their well-being. Our aim is to investigate the potential changes in the sexual activity and relationships of adolescents and young adults during the COVID-19 pandemic. In general, a decrease in sexual desire was reported during the COVID-19 pandemic, in both genders. Fewer sexual intercourses and bonding behaviors between partners were associated with loneliness and depressive symptoms. On the contrary, an increase in sexual desire was expressed in a few people, with masturbation to be the most preferable means of satisfaction. The present paper highlights the multifaceted impact of COVID-19 upon the sexual life of adolescents and young adults during the ongoing pandemic. The changes observed in their sexual activity and relationships, could provide the basis of future preventive and educational programs.